Ethnopharmacology of Souroubea sympetala and Souroubea gilgii (Marcgraviaceae) and identification of betulinic acid as an anxiolytic principle. (May 2015) - Puniani, Eva; Cayer, Christian; Kent, Pamela; Mullally, Martha; Sánchez-Vindas, Pablo; Poveda Álvarez, Luis; Cal, Victor; Merali, Zul; Arnason, John T.; Durst, Tony
Abstract : Graphical abstract: Extracts of Souroubea spp. showed anxiolytic activity in the elevated plus maze test in rats and betulinic acid was isolated as the active principle. Other phytochemicals isolated were 2-hydroxyursolic acid, taraxenyl trans-4-hydroxy-cinnamate, naringenin, methyl ursolate, eriodytiol, methyl 2-α-hydroxyursolate, methyl 2-α-hydroxymaslinate, methyl betulinate, and condrilla sterol. Highlights: Anxiolytic activity of a new medicinal genus, Souroubea was confirmed in the elevated plus maze with rats. An active principle, betulinic acid was isolated by bioassay guided techniques. Several new records of phytochemicals in the genus included phenolics and triterpenes. Abstract: The neotropical lianas Souroubea gilgii and Souroubea sympetala (Marcgraviaceae) were chosen for study as part of a phytochemical discovery strategy focusing on rare plant families in Central America. In participatory research, Q'eqchi' healers in Belize reported the use of these plants to reverse psychological symptoms inflicted by witchcraft. Extracts of two Souroubea species showed significant anti-anxiety activity in the elevated plus maze, a standardized test paradigm. Bioassay guided isolation led to the active principle, the pentacyclic triterpene, betulinic acid, which had activity in the elevated plus maze at 0.5 mg/kg. Other phytochemicals isolated included α- and β-amyrin, 2-hydroxyursolic acid, taraxenyl trans-4-hydroxy-cinnamate, naringenin, methyl ursolate, eriodytiol, methyl 2-α-hydroxyursolate, methyl 2-α-hydroxymaslinate, methyl betulinate, and condrilla sterol.